An Online safety monitoring system of hydropower station based on expert system. (July 2022) - Han, Zhang; Li, Yanling; Zhao, Zepeng; Zhang, Bo
Abstract: The hydropower station real-time safety monitoring is not only related to the safety, but also to the generation benefit of the power station. However, as the amount of monitoring data is very huge, and the dam structure is very complex, real-time monitoring cannot be carried out in most of the dam. It is useful to develop a high-performance safety monitoring system to assist the dam safety management work. As such, the paper introduces an expert system for dam safety management with a mode which can carry out the entire process of real-time dam safety monitoring, covering abnormal importing data, abnormal data changes, monitoring work, dam safety. The system has abundant functions such as dam safety analysis, visual query and remote consultation, etc. The system has been successfully applied to more than ten dam projects in China. The application shows that reliable data evaluation can identify data anomalies such as single point jump, multi point outlier and step change. Trend tracking can find possible structural changes. And clustering comprehensive evaluation can give a reasonable evaluation of the safety state of different parts of the dam. Complete online system can provide a supporting decision-making platform for the safety monitoring of the dams and improve the efficiency of power station management.